Transition metal oxide nanocatalysts for the deoxygenation of palm oil to green diesel - Guerrero-Corona, C. E.; Melo-Banda, J. A.; Lam-Maldonado, M.; Vega-Ibarra, L. A.; Diaz-Zavala, N. P.; Meraz-Melo, M. A. (Frontiers in Chemical Engineering, 2024)
This study investigated the hydrodeoxygenation of palm oil by different oxide nanocatalysts of transition metals α -Fe2O3, NiO, and NiFe2O4, which were synthesized by hot injection. All nanomaterials were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, and dynamic light dispersion. The catalytic evaluation was performed in a Parr-type reactor at 350°C, 3.5 MPa of H2 pressure, and 3 h of reaction. The liquid product obtained was analyzed by ultraviolet-visible light spectroscopy to identify the n-C16 generated during the reaction. The activity in the deoxygenation of fatty acids to produce n-C16 hydrocarbons has the following order: α-Fe2O3 < NiFe2O4 < NiO.